Challenges in accessing patient-centered care and patient empowerment in selected Ghanaian hospitals - Ruby V. Kodom; Robert T. Netangaheni (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Patient-centred care (PCC) and patient empowerment (PE) are crucial for better healthcare outcomes, in lower-middle-income countries like Ghana, which continues to encounter many challenges.